Witches and neighbours : the social and cultural context of European witchcraft - Briggs, Robin (Blackwell, 2002)
Witches and Neighbours is a highly original and unconventional analysis of a fascinating historical phenomenon. Unlike other studies of the subject which focus on the mechanisms of persecution, this book presents a rich picture of witchcraft as an all-pervasive aspect of life in early modern Europe. This book is not available from Blackwell in the United States and the Philippines.